Reduced visual acuity is mirrored in low vision imagery. (4th February 2021) - Arditi, Aries; Legge, Gordon; Granquist, Christina; Gage, Rachel; Clark, Dawn
Abstract : Research has examined the nature of visual imagery in normally sighted and blind subjects, but not in those with low vision. Findings with normally sighted subjects suggest that imagery involves primary visual areas of the brain. Since the plasticity of visual cortex appears to be limited in adulthood, we might expect imagery of those with adult‐onset low vision to be relatively unaffected by these losses. But if visual imagery is based on recent and current experience, we would expect images of those with low vision to share some properties of impaired visual perception. We examined key parameters of mental images reported by normally sighted subjects, compared to those with early‐ and late‐onset low vision, and with a group of subjects with restricted visual fields using an imagery questionnaire. We found evidence that those with reduced visual acuity report the imagery distances of objects to be closer than those with normal acuity and also depict objects in imagery with lower resolution than those with normal visual acuity. We also found that all low vision groups, like the normally sighted, image objects at a substantially greater distance than when asked to place them at a distance that 'just fits' their imagery field (overflow distance). All low vision groups, like the normally sighted, showed evidence of a limited visual field for imagery, but our group with restricted visual fields did not differ from the other groups in this respect. We conclude that imagery of those with low vision is similar to that of those with normal vision in being dependent on the size of objects or features being imaged, but that it also reflects their reduced visual acuity. We found no evidence for a dependence on imagery of age of onset or number of years of vision impairment.